Analysis of mastery of material concepts, narrative texts and procedure texts in class 4 MI Hidayatus Shibyan students - Oktavia Firanti, Firda; Saidah, Karimatus; Primasatya, Nurita (Universitas Nusantara PGRI Kediri, 2024)
This research aims to analyze the mastery of the concepts of narrative text and procedural text material in grade 4 students at MI Hidayatus Shibyan. This research uses descriptive qualitative methods. Data collection techniques were carried out through test, interview and documentation methods. Based on the results of the research that has been carried out, it can be concluded that class 4 students at MI Hidayatus Shyiban have not mastered the understanding of the concepts of narrative text and procedural text material. The narrative text and procedural text material possessed by students is still low. Factors involving student learning difficulties include teachers often using the lecture method, lack of learning innovation provided by teachers, decreased student enthusiasm for learning, and students' lack of mastery of the material. Therefore, there is a need for a solution in dealing with difficulties in mastering narrative text and procedural text material, namely; reading texts repeatedly in order to understand the material, increasing enthusiasm and interest in learning through the use of learning media and learning models, carrying out concrete learning in understanding procedural texts and procedural texts that can provide experience as well as understanding for students.